Energy efficiency and algorithm for selecting drives for technological machines - Andrenko, P.; Rogovyi, A.; Андренко, П. М.; Роговий, А. С. (Харківський національний автомобільно-дорожній університет, 2020)
Problem. The choice of the machine drive type at the design stage is a complex and multifaceted task, the correct solution of which largely depends on its technical level and operational qualities. The aim of the study is to identify the ways to increase the energy efficiency of technological machine drives and to develop an algorithm for selecting the drive type. Methodology. System analysis made it possible to analyze the environmental parameters in which it is appropriate to use a drive of one type or another, to develop criteria for comparing their application efficiency. The theory of automatic control methods made it possible to establish the drive characteristics. The theory of mechanisms and machines methods made it possible to determine the mass, size, and energy parameters of drives. Results. The main actions to improve the energy efficiency of technological machine drives are considered, an algorithm for choosing the drive type has been developed and a table has been created to compare the main consumer properties of drives. It has been established that the electrical drive of the executive elements is currently the main one in the area of mechatronic systems. It provides good control, easy feedback organization, high efficiency, and the best mass-dimensional efficiency. Originality. Considering the maximum number of factors, an algorithm for choosing the drive type has been developed. Criteria for comparing the efficiency of different drive types are proposed. Areas of effective application of electrical, hydraulic, pneumatic, and mechanical drives and their limiting output parameters are given. Practical value. Application of the developed algorithm reduces the time for selecting the drive type. In the future, it is necessary to supplement the existing database on the use of various drive types, based on the latest developments of their elements and circuit solutions, to develop new criteria for comparing drives of various types.
Енергоефективність та алгоритм вибору приводів технологічних машин
Keywords: hydraulic drive; mechanical drive; comparison criterions; efficiency criterions; characteristics; mechanical drive; гідравлічний привод; механічний привод; порівняння приводів; критерії ефективності; характеристики; механічний привод; гидравлический привод; механический привод; сравнение приводов; критерии эффективности; характеристики; механический привод; 621; 10.30977/AT.2219-8342.2020.47.0.84